Acute radiation mucosal reaction in patients with head and neck cancer - Wygoda, Andrzej; Składowski, Krzysztof; Sąsiadek, Wojciech; Hutnik, Marcin (Contemporary Oncology/Współczesna Onkologia, 2007)
The role of radiotherapy in the treatment of head and neck cancer patients is essential because of effectiveness comparable to surgery and, as a conservative modality, the possibility of organ preservation. The effect of radiation concerns not only tumours, but also normal, neighbouring tissues, which may lead to acute reactions. During radiotherapy of head and neck cancer patients, symptoms of acute mucosal reaction have the leading role determining tolerance of treatment. Successful conservative treatment of patients with advanced head and neck cancer very often requires aggressive methods of irradiation, such as unconventional schemes of dose fractionation or radio-chemotherapy. These therapeutic modalities intensify the cytotoxic effect, which leads to damage of large mucosal area and, in consequence, can cause marked deterioration of vital function. Although the course of acute mucosal reaction is similar for all irradiated patients, clinical observations show that escalation and duration of particular clinical parameters are individual. Some patients have good tolerance of irradiation, whereas others have to be hospitalized because of the need for intensive anti-inflammatory and supportive treatment due to mucositis. Here we present current knowledge on pathogenesis, evaluation and treatment of acute mucosal reaction based on literature and own experience.